2018
DOI: 10.1186/s12905-018-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

A community-based qualitative study on the experience and understandings of intimate partner violence and HIV vulnerability from the perspectives of female sex workers and male intimate partners in North Karnataka state, India

Abstract: BackgroundResearch has increasingly documented the important role that violence by clients and the police play in exacerbating HIV vulnerability for women in sex work. However few studies have examined violence in the intimate relationships of women in sex work, or drawn on community partnerships to explore the social dynamics involved. A community-based participatory research study was undertaken by community and academic partners leading intimate partner violence (IPV) and HIV prevention programs in Bagalkot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The analysis shows that women who have husbands/partners are more likely to use ANC. This is in line with the findings of several studies that have shown the role of a husband/partner in providing support for a woman's healthy lifestyle [32][33][34][35]. Some other studies actually encourage a husband to help improve a woman's health status by actively encouraging a healthier lifestyle [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…The analysis shows that women who have husbands/partners are more likely to use ANC. This is in line with the findings of several studies that have shown the role of a husband/partner in providing support for a woman's healthy lifestyle [32][33][34][35]. Some other studies actually encourage a husband to help improve a woman's health status by actively encouraging a healthier lifestyle [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…Research could also focus on other structural issues that our systematic review uncovered such as violence (Javalkar et al, 2019;Starmann et al, 2018), stigma, discrimination and the legal status of sex work as an occupation (Blanchard et al, 2018). These social, legal, and economic injustices not only contribute to sex workers' high risk of acquiring HIV but also substance abuse, and would be important to address (Rusakova, Rakhmetova, & Strathdee, 2015).…”
Section: Interventionsmentioning
confidence: 99%
“…In addition to harm-reduction research, literature recommends structural interventions in sex work contexts where substance abuse increases vulnerability to HIV including removal of legal barriers through the decriminalisation of sex work (Blanchard et al, 2018;Javalkar et al, 2019;Shannon et al, 2018;Starmann et al, 2018). Future research should, in particular, explore: (i) individual and contextual factors associated with substance use (initiation, promotion and continued use) among young people aged 18 years and below, in key population settings; (ii) pathways to substance use among under-researched groups such as uniformed personnel, truckers and miners, paying attention to the unique contribution of their work and work environments.…”
Section: Recommendationsmentioning
confidence: 99%
“…Change in perception is needed as a prevention effort from the impact of the practice of prostitution. 25,26 The government (Health Office) in addition to the need to pay attention to the availability of health workers, also needs an understanding that health workers cannot be separated from the influence of health belief. 27 Health workers are also part of the community, which cannot be separated from the local cultural context in which he lives.…”
Section: Discussionmentioning
confidence: 99%